A care-bundles approach to improving standard of care in AECOPD admissions: results of a national project. Issue 10 (21st July 2015) - Turner, AM; Lim, WS; Rodrigo, C; Welham, SA; Calvert, JM
Abstract : This report describes a care bundles implementation project for COPD undertaken during 2013 in England and Wales. High-level data were collected on outcomes of care for 11 748 patients admitted with an acute exacerbation of COPD (AECOPD). Patient-level data on processes and outcomes of care were collected on 3272 COPD admissions, among which 1174 bundles were delivered. Analysis demonstrated a statistically significant reduction in mortality and length of hospital stay from some bundle elements. Outcomes, including bundle completion rates, were better when specialist respiratory review occurred. The results support wider use of care bundles for AECOPD.